Review. Ugartemendia Eceizabarrena, Juan Ignacio, Interpretation in Accordance with European Union Law. Special Reference to the Constitutional Interpreter, Navarra, Aranzadi, 2023. - Mancini, Luna (Revista Internacional & Comparada de Derechos Humanos, 2024)
Interpretation in Accordance with European Union Law. Special Reference to the Constitutional Interpreter (Aranzadi, 2023), the latest book by Juan Ignacio Ugartemendia Eceizabarrena, stands as an important reference for scholars of constitutional issues and, in particular, for the doctrine of constitutional and conventional interpretation, not only in Europe.Although the study focuses on the current phase of the European integration process, updating issues related to the interpretation and argumentation of different sources of law is a classic subject that stems from questions such as: What does it mean to interpret? How are texts and norms related during the interpretive process? In what way is the activity of assigning meaning carried out? Is conformity or nonconformity found in rights, or are they properties that only interpreters can describe?